Avaliação da produção de leite e contagem de células somáticas em bovinos leiteiros suplementads com Saccharomyces cerevisiae como fonte de zinco orgânico - Coelho da Cunha Filho, Luiz Fernando (2007)
The aim of the evaluation of milk production and somatic cell count of dairy cow supplemented with Saccharomyces cerevisiae as a source of organic zinc for 180 days, 25 Holstein cows were selected, randomly chosen from a flock of 189 lactating cows. The animals were distributed in two groups, namely group 1 (G1) which holded 10 cows supplemented and group 2 (G2) with 15 animals without supplementation. The production of milk was measured by the control official milkman of the Assocition Paranaense of Creators of Bovine of the Holstein in seven moments during the 180 days. The samples of milk were collected of each animal, being submitted to the electronic counting of somatic cells. The results demonstrate that the supplemented of organic zinc didn't alter the production of milk, however it was capable to maintain low the counting of somatic cells. The data of the present work suggest that to use supplemented of organic zinc in the diet of cows milk, increase the quality of the produced milk and consequently the remuneration for the producer.